Online trading: issues and syariah perspective (OctaFX) - Abu Sin, Mohammad Syirazi; Mohd Nor, Syed Aiman Firdaus Syed; Azahar, Muhamad Daniel Hakimi; Mat, Muhammad; Razali, Muhammad Hushairie Fiqri (2023)
Online trading is the act of purchasing and selling financial products on the Internet. The trader buys and sells using an online trading platform. Online trading may include trading in bonds, stocks (shares), futures, international currencies, and other financial instruments. Most people trade online through an online broker. An online broker is a brokerage: firm that offers its services on the Internet. Unlike traditional brokers, the investor does not meet the broker face-to-face or via the telephone. Everything happens on the web. Online trading such as OctaFX. According to (Hatzakis et al., 2022), OctaFX was founded in 2011, OctaFX is part of a group of global entities, which include Octa Markets Incorporated (based in Saint Vincent and the Grenadines) and Octa Markets Cyprus Ltd (based in Cyprus). OctaFX has 229 tradeable symbols and a minimum deposit as low as $25 when funding with Visa/Mastercard.